Der Sinn des Mythos in Theologie und Hermeneutik - Schnelle, Udo (Evangelische Verlagsanstalt, 2023)
In his new book, the internationally renowned exegete Udo Schnelle outlines our understanding of myth from its beginnings to the present. He sees in myth an appropriate, and not outdated, form of speaking about God and the divine. One can speak of God only in images, metaphors and symbols, but above all in the form of myth as a meaning-giving narrative. Myths are fundamental stories that give order to life and provide orientation. A powerful myth preserves a surplus of knowledge and emotionality that goes beyond its temporal interpretations. It takes seriously the openness and incompleteness of reality and is open to God’s work in the world. Bultmann’s classification of myth as an inadequate way of speaking misses the essence and function of myth. Myth, as a narrative that creates meaning, is appropriate and at the same time indispensable – not only in theology, but also in hermeneutics. Just as history cannot be de-historicized and poetry de-poetized, so too the early Christian myth of the life, death and resurrection of the Son of God Jesus Christ cannot be demythologized. Rather, it must be interpreted on the premise of a positive understanding of myth and the conditions of modern, self-critical reason.